The anthropometric characteristics influence on the kinematic parametres of sprinter`s running - Blazevic, I.; Babic, V. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Children`s sprinter`s running is different from the adults` primarily because of the difference in motoric abilities, morphological characteristics, physiological and biochemical characteristics and psychological and sociological characteristics. This research`s aim has been to examine the anthropometric characteristics influence on the kinematic parameters of children`s sprinter`s running. Methods: The sample of variables consists of variables which determine the anthropometric characteristics (14 anthropometric variables) and 32 kinematic parameters of sprinter`s running. The kinematic parameters of sprinter`s running in its maximal speed phase have been gathered by applying the Optojump technology (Microgate, Italy) and the sprinter`s running times have been measured at each five metres on a 50 metres lap. Results: The results obtained from the multiple regression analysis between the group of anthropometric characteristics and results in the 50 metres lap running have shown that the percentage of boys` fatty tissue has been isolated as a statistically significant variable, while among girls the same variable is on the edge of statistical significance. In the boys` factor structure of anthropometric characteristics two factors have been isolated, while there were three of them among girls. The first factor found with boys and girls is the body voluminosity factor, the second factor found among boys is the longitudinal dimensionality factor, while the second factor found among girls is the factor of fatty tissue quantity. The third factor found among girls is the longitudinal dimensionality factor. Discussion: A negative connection to a higher percentage of fat or a higher quantity of subcutaneous fatty tissue with boys and girls has been determined for most of the variables. Boys with a lower quantity of subcutaneous fatty tissue achieve better results in the 50 metres running, have a shorter contact length, a longer duration of flight and a longer step length compared to boys with higher quantities of subcutaneous fatty tissue. Boys having better corporal muscular mass achieve a shorter contact length, a longer duration of flight and a longer step length. Girls with a lower quantity of subcutaneous fatty tissue achieve better results in the 50 metres running, have a shorter contact length and a longer step length.